The pharmacokinetics of letrozole and its effect on gonadotropins in anestrous ewes - Kivrak, Mehmet Bugra; Corum, Orhan; Alkan, Hasan; Atik, Orkun; Aydin, Ibrahim; Uney, Kamil (Elsevier BV, 2021)
The aim of this study was to determine the pharmacokinetics of letrozole and its effect on FSH and LH concentrations after single (IV, IM, SC) and repeated IV doses in anestrous ewes. This study was conducted in experiments 1 and 2 by randomly dividing 24 healthy Akkaraman ewes in anestrus into two equal groups. In experiment 1, the pharmacokinetics of letrozole following single IV, IM, and SC administration at 1 mg/kg dose and its effect of a single IV dose on plasma FSH and LH concentration were determined. In experiment 2, the effect of repeated IV doses of letrozole on FSH and LH concentrations was established. Plasma concentration of letrozole was measured using high-performance liquid chromatography, and pharmacokinetic parameters were calculated by non-compartmental analysis. FSH and LH concentrations were quantified using ELISA. The elimination half-life (t1/2ʎz) for IV, IM, and SC routes were 9.94, 37.29, and 41.07 h, respectively. The IV route for letrozole had a total clearance of 0.11 L/h/kg and a volume of distribution at a steady state of 1.50 L/kg. The peak plasma concentration was 0.11 μg/mL for the IM route and 0.14 μg/mL for the SC routes. The bioavailability was 55.18% for the IM route and 75.34% for the SC route. Letrozole following single and repeated (every 24 h for 3 days) IV administrations at 1 mg/kg dose did not affect LH concentration in anestrous ewes but caused an increase in the FSH concentration. This increase in FSH concentration may create a potential for the use of letrozole in ovarian superstimulation protocols. Favorable pharmacokinetic properties (long t1/2ʎz and good bioavailability) of letrozole for IM and SC routes require further investigation before use in estrus induction or estrus synchronization protocols in sheep.
Keywords: Sheep; Letrozole; Animals; Female; Follicle Stimulating Hormone; Luteinizing Hormone; Gonadotropins; Anestrus